2015
DOI: 10.5539/ibr.v8n8p129
|View full text |Cite
|
Sign up to set email alerts
|

A Consumer Perspective on Grocery Retailers’ Differentiation

Abstract: Increasing competition in the Italian grocery market is pressing retailers to search for new ways to differentiate themselves and gain a better competitive position in the mind of consumers. In this scenario, we intend to explore consumers" perception of grocery retailers in order to understand which store attributes consumers consider to be most important when choosing where to shop and which store attributes consumers perceive different between retail store formats and between grocery retailers. Our findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The findings of the current study partly agree with the findings of a study by Marques et al (2016), in that design/layout of the store and staff friendliness were identified as the most important supermarket attributes. The findings of the current study further concur with the study by Bellini et al (2015) in that shoppers consider the need to save time (easy access of store, store layout and self-service), therefore, for these shoppers, shopping quickly is important. Shopping to feel better is the least important motivation for visiting a supermarket.…”
Section: Shopping Motivations Determined By Supermarket Shoppers In Ssupporting
confidence: 90%
See 2 more Smart Citations
“…The findings of the current study partly agree with the findings of a study by Marques et al (2016), in that design/layout of the store and staff friendliness were identified as the most important supermarket attributes. The findings of the current study further concur with the study by Bellini et al (2015) in that shoppers consider the need to save time (easy access of store, store layout and self-service), therefore, for these shoppers, shopping quickly is important. Shopping to feel better is the least important motivation for visiting a supermarket.…”
Section: Shopping Motivations Determined By Supermarket Shoppers In Ssupporting
confidence: 90%
“…These independent retailers (such as informal spaza shops) are typically small, stock fast-moving items, operate at low profit margins and target shoppers with a lower LSM. With independent retailers becoming more profitable and sustainable, these retailers place supermarkets under competitive pressure; a supermarket may not view an independent retailer as a direct competitor despite both of them offering similar products (Bellini and Cardinali, 2015;Das Nair et al, 2015).…”
Section: The South African Supermarket Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers can also save time if display is logically organised and if store offers services that allow fast check-out such as self-scanning and self-check-out. As other reasons for choosing a particular grocery shop customers mention, named in the order of importance: quality of shopping experience, low prices and trust and loyalty to the retailer (Bellini & Cardinali, 2015). However, authors' findings further indicate that customers generally do not perceive significant difference between grocery retailers, implying that retailers should work on their differentiation in terms of meeting customer needs.…”
Section: When It Comes To Visual Merchandising What Not To Do Is Amentioning
confidence: 86%
“…This has intensified the competition and as a result "marketing strategies are changing too. Grocery retailers are developing new store formats aimed to capture the competitor's customers and expand their target market: discounters are improving the quality of the service to compete with the supermarkets and hypermarkets are developing lower pricing policies to compete with discounters" Bellini and Cardinali (2015).…”
Section: Literature Reviewmentioning
confidence: 99%